2009
DOI: 10.2471/blt.08.057075
|View full text |Cite
|
Sign up to set email alerts
|

Child maltreatment prevention: a systematic review of reviews

Abstract: Objective To synthesize recent evidence from systematic and comprehensive reviews on the effectiveness of universal and selective child maltreatment prevention interventions, evaluate the methodological quality of the reviews and outcome evaluation studies they are based on, and map the geographical distribution of the evidence. Methods A systematic review of reviews was conducted. The quality of the systematic reviews was evaluated with a tool for the assessment of multiple systematic reviews (AMSTAR), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
280
0
33

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 413 publications
(317 citation statements)
references
References 42 publications
4
280
0
33
Order By: Relevance
“…There is strong evidence from high-income countries that parenting programmes can reduce harsh and abusive punishment and reduce behaviour problems in children that are predictive of future perpetration of violence (Gilbert et al 2009;Kane, Wood, and Barlow 2007;Mikton and Butchart 2009). Emerging studies from low-and middle-income countries are showing similar results (Eshel et al 2006;Knerr, Gardner, and Cluver 2010).…”
Section: Family and Parenting Interventionssupporting
confidence: 61%
“…There is strong evidence from high-income countries that parenting programmes can reduce harsh and abusive punishment and reduce behaviour problems in children that are predictive of future perpetration of violence (Gilbert et al 2009;Kane, Wood, and Barlow 2007;Mikton and Butchart 2009). Emerging studies from low-and middle-income countries are showing similar results (Eshel et al 2006;Knerr, Gardner, and Cluver 2010).…”
Section: Family and Parenting Interventionssupporting
confidence: 61%
“…Three recent reviews of parenting programmes in LMICs found positive effects on direct measures of children's cognitive and language development across diverse policy, service delivery, and social contexts. (23)(24)(25). We updated and expanded on the previous reviews by conducting a meta-analysis of non-cognitive outcomes and concluded that parenting programmes increased scores on measures of psycho-social development (SMD 0·35, 95% CI 0·14-0·56, 13 studies) and motor development (SMD 0.13, 95% CI 0·07-0·19, 9 studies), in addition to child cognitive development (SMD 0.36, 95% CI 0·22-0·49, 19 studies).…”
Section: Parenting Supportmentioning
confidence: 99%
“…For example, including stimulation in nutrition programmes can improve developmental outcomes, which cannot be fully promoted through nutrition interventions alone. (23) Breastfeeding is an example of an intervention, which combines elements of nutrition with bonding.…”
Section: In Summary: Nurturing Care and Protection Can Mediate Risk Fmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29][30][31][32][33][34][35] Some home visitation experts caution that potential program impacts on maltreatment may be obscured by "surveillance effects" because families receiving home visitation (ie, the intervention group) have regular contact with professionals or paraprofessionals who might identify and report instances of maltreatment, whereas families not participating in the program (ie, the control group) are not exposed to the same level of scrutiny. 24,36 The mixed nature of findings for these home visitation programs suggests that the next step is to determine which program strategieswork best for whom and under what conditions.…”
Section: Discussionmentioning
confidence: 99%